Handbook of Hydrothermal Technology (2nd Edition) - Byrappa, K.; Yoshimura, Masahiro (Elsevier, 2013)
Quartz, zeolites, gemstones, perovskite type oxides, ferrite, carbon allotropes, complex coordinated compounds and many more -- all products now being produced using hydrothermal technology. This book brings together the latest techniques in this rapidly advancing field in one exceptionally useful, long-needed volume. The Handbook provides a single source for understanding how aqueous solvents or mineralizers work under temperature and pressure to dissolve and recrystallize normally insoluble materials, and decompose or recycle any waste material. The result, as the authors show in the book, is technologically the most efficient method in crystal growth, materials processing, and waste treatment. Evolution of the technology from geology to widespread industrial use. Descriptions of equipment used in the process and how it works. Problems involved with the growth of crystals, processing of technological materials, environmental and safety issues. Analysis of the direction of today's technology. In addition, readers get a close look at the hydrothermal synthesis of zeolites, fluorides, sulfides, tungstates, and molybdates, as well as native elements and simple oxides. Delving into the commercial production of various types, the authors clarify the effects of temperature, pressure, solvents, and various other chemical components on the hydrothermal processes.Gives an overview of the evolution of Hydrothermal Technology from geology to widespread industrial useDescribes the equipment used in the process and how it worksDiscusses problems involved with the growth of crystals, processing of technological materials, and environmental and safety issues